Suplementação com cana de açúcar e capim Napier na alimentação de avestruzes na fase de engorda: desempenho produtivo e digestibilidade - Adelina Aichinger (2008)
This project aimed to elaboration of two trials, one with productive performance and other with aparent digestiibility with ostrich in fattening stage, utilizing sugar cane and napier grass diets to supplement pelleted concentrate. The experiment of productive performance were utilized 61 ostriches of African Black / Blue Neck species, both sex, with the minimum six months of age, shared in four pickets and two weight categories.Was utilized a completely randomized design was used in 2x2x2 factorial (weight categories, diets and sex), with unbalanced repetitions where was evaluated the total gain weight of the animals being the feed intake and feed conversion estimated. The means were compared by Student’sNewman-Keuls test (p < 0,05). The categories of weight were established with the weight inicial under 60 kg, with 55,16 kg mean and other with above 60kg, with 68,39 kg mean. The apparent digestibility trial, the completely randomized design was used in 2x2 factorial (diet and sex), with 18 repetitions and means were compared by Student’s-Newman-Keuls test (p < 0,05). The animals utilized in the apparent digestibility trial were come from the productive performance trial. This experiment was aimed for evaluated and validated the lignin purified and improved (LIPE®) utilization like external indicator of digestibility , compared the total faeces collect method (p < 0,05), in ostrichs fattening stage, started from six months and 72,39 kg of mean weigth. The gains weight and apparent digestibility of the diets results showed the supplement with sugar cane in ostrich of fattening stage alimentation was superior the napier grass and the LIPE® can be validated like external indicator in digestibility determination of the nutrients for ostriches, was equivalent with the total faeces collect.